Differential gene expression associated with inflammation in peripheral blood cells of patients with pneumoconiosis. Issue 4 (22nd July 2016) - Liu, Shu‐jun; Wang, Ping; Jiao, Jie; Han, Lin; Lu, Yu‐min
Abstract : Objectives: To study expression changes in inflammation‐related genes in peripheral blood of patients with pneumoconiosis and to explore the possibility of these genes as pneumoconiosis biomarkers. Methods: Peripheral blood samples of patients with pneumoconiosis patients and controls were collected, and total RNA of the blood cells were extracted and reverse transcribed to cDNA. Screenings of deferentially expressed genes associated with inflammation between patients with pneumoconiosis and controls were performed using real‐time quantitative PCR array and the expressions of the three most upregulated genes were confirmed by real‐time PCR. Results: The expression of 11 genes was significantly altered in patients with pneumoconiosis compared with those of the control. Among these 11 genes, 8 genes were upregulated and 3 were downregulated. Preliminary results indicated that interleukin 6 (IL‐6) mRNA expression in patients with pneumoconiosis was higher than that in controls (P=0.019). The level of IL6 mRNA expression in the patients was higher than that in non‐smoking controls, but it was neither affected by type and stage of pneumoconiosis nor by time of contact with dust. Conclusions: IL6 was possibly involved in the development of pneumoconiosis.